PENANAMAN PENDIDIKAN KARAKTER DISIPLIN DAN KERJA KERAS MELALUI EKSTRAKURIKULER DRUM BAND - Chafifah Kinteki, Ridha; Utomo, Arief Cahyo (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2023)
This research is an effort to instill discipline and hard work character education through drum band extracurricular activities at SDN 3 Slahung Ponorogo. This research uses a qualitative approach. Data collection methods are observation, interviews and documentation. The data analysis techniques in this research are data reduction, data display and drawing conclusions. The results of the research show that instilling the value of character education of discipline and hard work through drum band extracurricular activities at SDN 3 Slahung Ponorogo is; 1) instilling the value of disciplined character, trainers schedule training after learning is finished to anticipate students being late for training, returning tools to their storage place in turns and obeying agreed rules; 2) strengthening the character of hard work is raising students' emotional awareness of their own values ??by thinking rationally; 3) The obstacles that occur when instilling the characteristic values ??of discipline and hard work in extracurricular drum band are students who lack concentration at certain times and weather conditions.